IDENTIFICATION OF CONSTRAINTS AND THE ROLE OF EXTENSION WORKERS IN INNOVATION IN WELTH RICE CULTIVATION IN THE RESPONSE TO CLIMATE CHANGE IN NORTH ACEH DISTRICT - Setia Budi; Eva Wardah; Nopri Yanto (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Climate change has affected rice productivity in North Aceh Regency, characterized by rainfall fluctuations, increased temperatures, and disruption of agricultural ecosystems. This study aims to identify obstacles faced by farmers in implementing innovations in rice cultivation and analyze the role of agricultural extension workers in supporting adaptation to climate change. The method used in this study was a survey method with qualitative descriptive analysis of 80 respondents in North Aceh Regency. The results showed that the main obstacles included limited adaptive superior seeds (86.56%), availability of irrigation water (80.63%), and low climate literacy (78.24%). The role of adaptive extension workers was assessed as "instrumental" with an average index value of 69.71%, the highest score for the extension worker variable as an innovator (78.63%) and extension workers as educators with an index value of (75.08%). The results of this study emphasize the importance of extension workers as agents of change in terms of technology transfer, climate education, and facilitating access to resources. Community-based extension strategies and participatory approaches have proven effective in increasing farmers' adaptive capacity. The importance of strengthening the role of extension workers through training, policy support, and cross-sector collaboration to accelerate the adoption process of innovations in rice cultivation that are resilient to climate change.